2011
DOI: 10.1002/ptr.3409
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Medicinal Plants from Iranian Traditional Medicine for Acetylcholinesterase Inhibition

Abstract: To find new herbal compounds with an acetylcholinesterase (AChE) inhibitory effect, this study focused on herbal drugs and resins which have been used in Iranian traditional medicine for the treatment of cognitive disorders. Forty drugs were selected from authoritative written documents of Iranian traditional medicine. Each drug was extracted by accelerated solvent extraction using dichloromethane followed by methanol. The 80 extracts were screened for AChE inhibitory activity by a TLC bioautography method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 20 publications
(21 reference statements)
0
32
0
Order By: Relevance
“…Detection was performed with anisaldehyde-sulfuric acid reagent to determine the chemical composition of the extract. In addition, a TLC bioautography screening assay was performed for AChE inhibitory activity according to a published method under use of the same stationary and mobile phase and very thorough removal of the mobile phase under airstream before detection (Marston et al, 2002;Adhami et al, 2011). Chelidonine served as a positive control showing Rf 0.45 in this system.…”
Section: Tlc Bioautography Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Detection was performed with anisaldehyde-sulfuric acid reagent to determine the chemical composition of the extract. In addition, a TLC bioautography screening assay was performed for AChE inhibitory activity according to a published method under use of the same stationary and mobile phase and very thorough removal of the mobile phase under airstream before detection (Marston et al, 2002;Adhami et al, 2011). Chelidonine served as a positive control showing Rf 0.45 in this system.…”
Section: Tlc Bioautography Assaymentioning
confidence: 99%
“…Pharmacological studies have shown several biological activities for Semecarpus anacardium such as anti-inflammatory (Bhitre et al, 2008), antiatherogenic (Sharma et al, 1995), anti-oxidant (Pal et al, 2008), anti-microbial (Gajjar et al, 2009), hypoglycemic (Kothai et al, 2005), hypolipidemic (Jaya et al, 2010), anti-carcinogenic (Nair et al, 2009) and anti-spermatogenic effects (Sharma et al, 2003). Methanolic and dichloromethane (DCM) extracts from the fruit resin of Semecarpus anacardium were among the most potent hits for AChE inhibition in a screening of plants used for the enhancement of cognitive performance and treatment of memory loss in ITM (Adhami et al, 2011). In this study, an activity-guided approach was applied to isolate and characterize the components with AChE inhibitory activity.…”
Section: Introductionmentioning
confidence: 97%
“…Harmala alkaloids (HAlks) are a family of compounds with pharmacological and psychopharmacological effects on humans [1][2][3][4]. They are especially renowned for their antidepressant properties, because they are strong inhibitors of monoamine oxidase type A (MAO-A) enzyme, which catalyzes the oxidative deamination of biogenic amines and neurotransmitters [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, there is a clear trend towards the use of the TLC bioautography technique as a method for screening active compounds against microorganisms rather than a method for the detection of enzyme activities or inhibitors. The use of TLC (bio)autography was reported for the screening of inhibitors of acetylcholinesterase [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , butyrylcholinesterase 12,16,22,23,27 , dipeptidyl peptidase IV 28 , glucose-6-phosphate dehydrogenase 29 , a-and b-glucosidases [30][31][32][33][34] , lipase [35][36][37] , monoamine oxidases A and B 38,39 , DNA topoisomerase I 40 , tyrosinase [41][42][43] and xanthine oxidase 44 . To date, the use of the TLC-based autographic method for the detection of PGI inhibition has only been developed for a biocatalyst isolated from the reference E. coli strain ATCC (American Type Culture Collection) 25922 45 .…”
Section: Introductionmentioning
confidence: 99%